TEACHERS’ AND STUDENTS’ PERCEPTIONS ON AN ENGLISH COURSEBOOK USED IN EFL CLASSROOM - Khairunnisa Dwinalida (BABASAL English Education Journal, 2023)
Notwithstanding the importance of a coursebook in the teaching-learning process, there are certain preliminary issues with the official English coursebooks offered in line with the implementation of the 2013 curriculum. Investigating some perceptions of the coursebooks from the perspectives of students and teachers is vital in light of that issue. The participants in the study were two teachers and 14 students. Frequency analysis and interview analysis were used to evaluate the quantitative data that was gathered from the students using closed-ended questionnaires and the qualitative data that was gathered from the teachers using open-ended questionnaires. The students' favorable opinions may not come as much of a surprise, but the teachers' harsh judgments are surprising discoveries. The inference is that teachers have different perceptions than do students. Different opinions among teachers and students may contribute to discussions on how to make the most of it, suggest desirable changes in teaching methods, and call for government adjustment. Similar to this, it is recommended that teachers might be inspired to encourage students to use the book to enhance in their English language learning if they have positive opinions about it.